2023
DOI: 10.3390/biom13030465
|View full text |Cite
|
Sign up to set email alerts
|

CAR-T Cells in the Treatment of Ovarian Cancer: A Promising Cell Therapy

Abstract: Ovarian cancer (OC) is among the most common gynecologic malignancies with a poor prognosis and a high mortality rate. Most patients are diagnosed at an advanced stage (stage III or IV), with 5-year survival rates ranging from 25% to 47% worldwide. Surgical resection and first-line chemotherapy are the main treatment modalities for OC. However, patients usually relapse within a few years of initial treatment due to resistance to chemotherapy. Cell-based therapies, particularly adoptive T-cell therapy and chime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 207 publications
(235 reference statements)
0
5
0
Order By: Relevance
“…As depicted in Fig. 3C , in the presence of DDP, cancer cells transduced with Ad-siERCC1 (74.19%) exhibited significantly lower cell viability compared with those transduced with Ad-NC (56.85%) six days post-transduction (Independent-Samples t test; t ( 6 ) =−7.420; P<0.001). Additionally, cell cycle analysis revealed that SKOV3 cells in all groups were arrested in the G 1 phase when compared with the control group (control group: 46.60%; Ad-NC: 63.79%; Ad-siERCC1: 66.05%; DDP: 68.42%; DDP + Ad-NC: 70.56%; DDP + Ad-siERCC1: 75.12%; one-way ANOVA, G 1 : F ( 5 , 12 )= 148.758, P<0.001; vs. the control group, Ad-NC: P<0.001; Ad-siERCC1: P<0.001; DDP: P<0.001; DDP + Ad-NC: P<0.001; DDP + Ad-siERCC1: P<0.001).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…As depicted in Fig. 3C , in the presence of DDP, cancer cells transduced with Ad-siERCC1 (74.19%) exhibited significantly lower cell viability compared with those transduced with Ad-NC (56.85%) six days post-transduction (Independent-Samples t test; t ( 6 ) =−7.420; P<0.001). Additionally, cell cycle analysis revealed that SKOV3 cells in all groups were arrested in the G 1 phase when compared with the control group (control group: 46.60%; Ad-NC: 63.79%; Ad-siERCC1: 66.05%; DDP: 68.42%; DDP + Ad-NC: 70.56%; DDP + Ad-siERCC1: 75.12%; one-way ANOVA, G 1 : F ( 5 , 12 )= 148.758, P<0.001; vs. the control group, Ad-NC: P<0.001; Ad-siERCC1: P<0.001; DDP: P<0.001; DDP + Ad-NC: P<0.001; DDP + Ad-siERCC1: P<0.001).…”
Section: Resultsmentioning
confidence: 92%
“…At MOI=10, the mRNA and protein levels of ERCC1 were validated using RT-qPCR and immunoblotting techniques, revealing a decrease in ERCC1 mRNA (~60% less than control; Independent-Samples t test; t ( 6 ) =36.842; P<0.001; Fig. 2B ) and protein (>3-fold less than control) (Independent-Samples t test; t ( 6 ) =24.036; P<0.001; Fig. 2C ) upon Ad-siERCC1 treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…OC is a type of malignant cancer that starts in the ovaries, which are part of the female reproductive system (Kossai et al, 2018). In addition to traditional treatment strategies, such as surgery, chemotherapy, and radiation therapy, immunotherapy and targeted therapy are also available for the clinical treatment of OC patients (Kurnit et al, 2021; Zhang et al, 2023). However, immunotherapies show less success in OC, and the use of immunotherapy is limited by immune profiling of OC patients, such as mismatch repair and homologous repair deficiency (Morand et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that tumor metastasis is the main risk factor for ovarian cancer progression, and the polymorphism of genes regulating OC metastasis participates in OC pathogenesis. [ 5 , 6 ] Single nucleotide polymorphism is a common form of gene variation, with one single nucleotide polymorphism locus for every 1000 nucleotides, which has a crucial role in the tumor pathogenesis. The abnormal expression of matrix metalloproteinase-3 (MMP-3) participates in the occurrence of OC.…”
Section: Introductionmentioning
confidence: 99%